Aggregation-induced photothermal effects of far-red probes in non-covalent supramolecular assemblies - Lim, Jin Heng (Nanyang Technological University, 2023)
This thesis reports the use of various supramolecular assemblies to improve the photothermal (PT) effects of a photothermal agent (PTA). In Chapter 2, attempts were made to improve the PT effect of the PTA by incorporating it in phospholipid liposomes and polymeric micelles. The PT effect was measured using the temperature change achieved by the PTA under irradiation. It was found that the PT effect achieved was hindered by the phase transition property of the liposome and micelle where heat generated by the PTA was absorbed for the crystalline-gel and sol-gel transitions by the liposomes and micelles respectively. Chapter 3 dealt with the incorporation of the PTA in hydrogels. The PT effect of PTA under irradiation was studied in micellar and polymeric hydrogels. It was determined that the polymeric hydrogel was the ideal supramolecular assembly for improving the PT effects of the PTA while micellar hydrogels did not provide an environment that allowed effective aggregation of PTA which led to unsuccessful heat generation under irradiation.